Quantitative Immunofluorescence of Regulated eps Gene Expression in Single Cells of Ralstonia solanacearum - Kang, Yaowei (American Society for Microbiology, 1999)
Ralstonia solanacearum, a phytopathogenic bacterium, uses an environmentally sensitive and complex regulatory network to control expression of multiple virulence genes. Part of this network is an unusual autoregulatory system that produces and senses 3-hydroxypalmitic acid methyl ester. In culture, this autoregulatory system ensures that expression of virulence genes, such as those of the eps operon encoding biosynthesis of the acidic extracellular polysaccharide, occurs only at high cell density (>10(7) cells/ml). To determine if regulation follows a similar pattern within tomato plants, we first developed a quantitative immunofluorescence (QIF) method that measures the relative amount of a target protein within individual bacterial cells. For R. solanacearum, QIF was used to determine the amount of β-galactosidase protein within wild-type cells containing a stable eps-lacZ reporter allele. When cultured cells were examined to test the method, QIF accurately detected both low and high levels of eps gene expression. QIF analysis of R. solanacearum cells recovered from stems of infected tomato plants showed that expression of eps during pathogenesis was similar to that in culture. These results suggest that there are no special signals or conditions within plants that override or short-circuit the regulatory processes observed in R. solanacearum in culture. Because QIF is a robust, relatively simple procedure that uses generally accessible equipment, it should be useful in many situations where gene expression in single bacterial cells must be determined.